Pan-cancer convergence of tumour–immune microenvironment motifs revealed by CyTOF and imaging mass cytometry - Vallée, Alexandre; Drezet, Alexandre; Arutkin, Maxence (Frontiers in Immunology, 2025)
Mass cytometry (CyTOF) and Imaging Mass Cytometry (IMC) provide single-cell resolution for over 50 protein markers, enabling unprecedented exploration of tumour and immune heterogeneity. We conducted a scoping review of 61 original studies (inception–2025), spanning 17 cancer types, to map current applications, analytical strategies, and emerging biological insights. 46 studies used CyTOF alone, 12 employed IMC exclusively, and 3 combined both platforms. Median panel sizes were 33.5 markers for CyTOF and 33 for IMC. While lineage and immune checkpoint markers were universal, phospho-epitopes, metabolic enzymes, and stromal proteins appeared in more focused subsets. Most studies followed a three-step analytical workflow: (i) segmentation or gating, (ii) unsupervised clustering, and (iii) downstream spatial or functional analyses. CyTOF investigations frequently identified exhausted CD8+ T-cell subsets (e.g., PD-1+TIM-3+CD39+), suppressive myeloid populations (e.g., CD163+HLA-DR− macrophages), and metabolically reprogrammed Tregs. IMC studies uncovered spatial patterns predictive of outcome, such as tertiary lymphoid structures (TLSs) and macrophage–T cell exclusion zones. Several studies proposed predictive immune signatures or integrated CyTOF with transcriptomic or spatial datasets. We identified five recurrent immunobiological motifs, CD8+ T-cell bifurcation, CD38+ TAM barriers, TLS maturity, CTLA-4+ NK-cell signatures and metabolically defined niches, highlighting convergent axes of resistance and response. Bioinformatic pipelines converged around FlowSOM or PhenoGraph clustering, CITRUS or elastic-net feature selection, and increasingly, machine learning and agent-based spatial modelling. Collectively, CyTOF and IMC are redefining biomarker discovery, therapeutic stratification, and virtual trial design in oncology, establishing high-dimensional CyTOF as a cornerstone of next-generation precision cancer medicine.